PENGEMBANGAN E-MODUL BERBANTUAN BOOKCREATOR PADA MATERI BUNYI DAN SIFATNYA - Resyi Abdul Gani; Rohayati; Shahiril Anwar, Wawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Development of E-Modules Using Book Creator on Sound Materials and Their Properties. This research aims to create e-module teaching materials using book creators on sound materials and their properties in improving the learning outcomes of grade V students of SDN Pamijahan 01, Bogor Regency which totals 20 students. The product development of this research uses a 4D model (Define, Design, Development, Dessiminate) but the development of this e-module is up to the development stage. Data analysis techniques began to analyze the needs of teachers, students, and curriculum analysis, make product designs, develop e-module products by conducting expert validation and limited trials of respondents. The results of media validation, linguists, and material experts show that the e-module using a book creator is valid and very feasible to use in learning by obtaining an average percentage of 92%. In the trial stage, it was limited to 20 students, giving very good respondents and deserving of an average percentage of 90%. Based on the results of the research, it can be concluded that the e-module using this book creator is proven to be valid and can improve students' learning outcomes in understanding the learning material.